Environmental Self‐Adaptive Wind Energy Harvesting Technology for Self‐Powered System by Triboelectric‐Electromagnetic Hybridized Nanogenerator with Dual‐Channel Power Management Topology. Issue 43 (13th September 2022) - Yong, Shun; Wang, Hanqing; Lin, Zenan; Li, Xiaosa; Zhu, Boyu; Yang, Lijun; Ding, Wenbo; Liao, Ruijin; Wang, Jiyu; Wang, Zhong Lin
Abstract: Natural wind energy harvesting enables a far‐reaching and sustainable solution to supply pervasive sensors in the Internet of Things (IoT). Electromagnetic generators (EMGs) struggle to harvest energy from breezes, which causes regrettable energy wastage. Herein, a triboelectric‐electromagnetic hybridized nanogenerator (TEHG) is designed with a dual‐rotor structure to consolidate harvesting band for high efficiency of triboelectric nanogenerators (TENGs) in breeze and the EMG in high wind speeds. The TEHG performs an efficient energy collection (41.05 W m −3 ) and a smooth output in the wind speed of 2−16 m s −1, attributed to the environmental self‐adaptive cooperation between TENGs and EMGs. The TENG output power contribution is more than 70% at low wind speeds (<5 m s −1 ). Moreover, a dual‐channel power management topology (DcPMT) is established to co‐manage outputs of two modules in TEHG. By virtue of the DcPMT hierarchically combining the isolated storage with undervoltagelockout strategy, the TEHG steadily supplies a standardized 3.3 V voltage for commercial electronics. Furthermore, a TEHG‐based self‐powered system is demonstrated for driving sensors to monitor meteorological information. The TEHG with DcPMT is advantageous in broad‐band and high‐efficiency of wind energy harvesting, thus exhibiting a great potential for elevating the environmental self‐adaptability and stability margin of the IoT. Abstract : The proposed triboelectric‐electromagnetic hybridized nanogenerator (TEHG)‐based self‐powered system incorporates a dual‐channel power management topology (DcPMT) with high energy conversion performance (16.5 mW) for wide wind speeds (2−16 m s −1 ), attributed to environmental self‐adaptive cooperation between the triboelectric nanogenerator and electromagnetic generator modules. By virtue of the DcPMT hierarchically combining the isolated energy storage with the undervoltage‐lockout strategy, the TEHG can steadily supply a standardized voltage (3.3 V) for commercial electronics.